Method for continuous multiscale representation of terrain contours using T‐spline technique. Issue 7 (12th September 2022) - Qian, Haoyue; Yang, Lin; Zuo, Zejun; Wang, Yu; Yang, Ni; Zhou, Shunping; Yang, En
Abstract: Contours are the main graphical element for characterizing three‐dimensional terrain on a topographic map. Continuous multiscale representation of contours is crucial to meet users' needs for detailed information between fixed‐scale contours. Wherein shape of the contour should ideally progressively change as the scale continuously changes. However, the lack of a bridge between scale and shape deformation degrees is an obstacle in obtaining continuous multiscale contours. A novel method for continuous multiscale representation of contour based on T‐spline (CMRTS) is proposed. Multiscale contours are generated through interpolation of the T‐spline and constraint of the relationship between scale and shape similarity. First, a T‐spline surface is established using two fixed‐scale contours. Second, the T‐spline surface intersects a set of horizontal planes with gradual heights to generate intersecting lines. Finally, the quantitative relationship between the scale and shape similarity is determined to align each intersecting line with the corresponding scale and achieve continuous multiscale contours. A case study in Chongqing, China implements and evaluates the proposed method. Results indicate that shape changes of contours generated by CMRTS are more natural and progressive than those by two typical methods. Our method shows high potential and practicability for mapping continuous multiscale contours for real‐world terrain applications.